Phonetic and Phonological Comparison between Batusangkar sub-dialect and Lintau Buo sub-dialect - Lailatul Rahmi; Rusdi Noor Rosa (Universitas Negeri Padang, 2019)
This research investigates the comparison between Batusangkar sub-dialect and Lintau Buo sub-dialect, which focuses on phonetic and phonological aspects. The aim of this study is to identify the types of sound changes that occur between two sub-dialects in the same language from phonetic and phonological aspects. This research used a descriptive method. The researcher used elicitation techniques in conducting interviews to collect data from each informant. The results of this study indicate that there are 13 sound changes, which are divided into 5 vowel changes, that are [a] to [əʊ], [ɪ], [ə], and [ɑ:] to [ɔ:]. Then, 4 consonant changes, that are [k] to [ɳ], [r] to [w] and [ɰ], and [t] to [m], and 4 diphthong changes, that are [ɪa] to [ɪə] and [ɪʊ], [ʊa] to [ʊə] and [ʊ]. In addition, there are sound changes caused by phonological processes; assimilation, dissimilation, insertion, and deletion. Furthermore, there are several words that have full vocabulary changes. The results show that the pronunciation between the two sub-dialects is different. The significant changes occurred when the word in sound [a] in Batusangkar sub-dialect is changes to [o] in Lintau Buo sub-dialect and the word, which have a phonological process that is deletion.